2014
DOI: 10.3126/ajms.v6i1.10147
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and the levels of liver enzymes (ALT, AST & GGT) in East Medinipur, India

Abstract: Objective Obesity is a common disorder in our country. Most widely used method to gauge obesity is Body Mass Index (BMI) which is equal to weight in kilogram divided by height in meter square. The objective of our study was to find the levels of liver enzymes ALT, AST & GGT in two groups (overweight individuals and obese individuals). Methods: A total no of 156 individuals were selected for the study and they were categorized into three groups on the basis of BMI- Group I Normal, BMI 18.5 to 24.9 (n=72), G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…In contrast, no effect was observed for decreased BMI on serum ALT and AST levels 54 . In another study, ALT, AST and GGT levels were found to be higher in obese individuals but these liver enzymes did not show any significant correlation with obesity 55 . These inconsistent findings may reflect the differences of population groups between the studies.…”
Section: Discussionmentioning
confidence: 85%
“…In contrast, no effect was observed for decreased BMI on serum ALT and AST levels 54 . In another study, ALT, AST and GGT levels were found to be higher in obese individuals but these liver enzymes did not show any significant correlation with obesity 55 . These inconsistent findings may reflect the differences of population groups between the studies.…”
Section: Discussionmentioning
confidence: 85%
“…Serum GGT showed a significant association with both general and abdominal obesity 34 . Das et al found that ALT, AST and GGT levels were higher in individuals with obesity, but no direct association was found between these liver enzymes with obesity 35 …”
Section: Discussionmentioning
confidence: 98%
“…Free radicals will interfere with the integrity of the hepatocyte membrane, thus eliminating various enzymes from hepatocytes (Ryeo-Eun et al, 2016). Obesity can interfere with liver function due to NAFLD, which causes damage to liver cells, which then results in increased activity of the enzymes AST, ALT, and ALP (Das et al, 2015).…”
Section: Effect Of Scenedesmus Dimorphus On Liver Functionmentioning
confidence: 99%